The use of LMS Moodle to Improve Reading Comprehension Skill for the 10th Grade Students - Oetomo, Tyas; Musyarofah, Lailatul; Widodo, J. Priyanto (Jurnal Basicedu, 2022)
The purpose of this research was to increase students' achievement in reading comprehension by implementing the LMS Moodle to the 10th grade students at SMA Petra 4 Sidoarjo in the academic year 2020/2021. Classroom Action Research (CAR) was applied in conducting this study from January to June 2021. Each cycle of CAR consisted of four steps: planning, action, observation, and reflection. The data were gathered through the use of two instruments: observation and test. The results indicated that students made great progress in their ability to comprehend the reading texts. Pre-test mean score was only 72.71, but improved to 79.29 in cycle 1 and 86.57 in cycle 2. The lowest pre-test score was only 65 and improved to 70 to 75 in subsequent cycles. Meanwhile, the highest pre-test score was 82.5, and the highest post-tests scores were 92.5 and 95. In case of the students who passed the tests, while only 9 students (25.71%) passed the pre-test, there were significant improvements in post-tests, with 21 students (60%) passing in post-test cycle 1 and 33 students (94.29%) passing in post-test cycle 2. This research was stopped in cycle 2 due to the fact that the criteria for success were met in a percentage of 94.29%, with 33 students passing the post-test in cycle 2, based on the Minimum Mastery Criteria (KKM) standard of > 76